Gauge theory applied to magnetic lattices. (1st November 2022) - Di Pietro, A.; Ansalone, P.; Basso, V.; Magni, A.; Durin, G.
Abstract: The generalizations of micromagnetic exchange including higher order interactions are normally performed phenomenologically. In this paper we combine graph and gauge field theory to provide a new procedure to perform the continuum limit of the Heisenberg model. Our approach allows to simultaneously account for the symmetries of the crystal, the effect of spin-orbit coupling and their interplay. We obtain a micromagnetic theory accounting for the crystal symmetry constraints at all orders in exchange. The form of the micromagnetic Dzyaloshinskii-Moriya interaction in all 32 point groups is calculated at the first order.